Characterization of heat emission of light-curing units - Mohammed A. Wahbi; F.A. Aalam; F.I. Fatiny; S.A. Radwan; I.Y. Eshan; K.H. Al-Samadani (Saudi Dental Journal)
Objectives: This study was designed to analyze the heat emissions produced by light-curing units (LCUs) of different intensities during their operation. The null hypothesis was that the tested LCUs would show no differences in their temperature rises. Methods: Five commercially available LCUs were tested: a “Flipo” plasma arc, “Cromalux 100” quartz–tungsten–halogen, “L.E. Demetron 1” second-generation light-emitting diode (LED), and “Blue Phase C5” and “UltraLume 5” third-generation LED LCUs. The intensity of each LCU was measured with two radiometers. The temperature rise due to illumination was registered with a type-K thermocouple, which was connected to a computer-based data acquisition system. Temperature changes were recorded in continues 10 and 20 s intervals up to 300 s. Results: The Flipo (ARC) light source revealed the highest mean heat emission while the L.E. Demetron 1 LED showing the lowest mean value at 10 and 20 s exposure times. Moreover, Cromalux (QTH) recorded the second highest value for all intervals (12.71, 14.63, 14.60) of heat emission than Blue Phase C5 (LED) (12.25, 13.87, 13.69), interestingly at 20 s illumination for all intervals the highest results (18.15, 19.27, 20.31) were also recorded with Flipo (PAC) LCU, and the lowest (6.71, 5.97, 5.55) with L.E. Demetron 1 LED, while Blue Phase C5 (LED) recorded the second highest value at the 1st and 2nd 20 s intervals (14.12, 11.84, 10.18) of heat emission than Cromalux (QTH) (12.26, 11.43, 10.26). The speed of temperature or heat rise during the 10 and 20 s depends on light intensity of emitted light. However, the QTH LCU was investigated resulted in a higher temperature rise than LED curing units of the same power density. Conclusion: The PAC curing unit induced a significantly higher heat emission and temperature increase in all periods, and data were statistically different than the other tested groups (p < .05). LED (Blue Phase C5) was not statistically significant (p < .05) (at 10 s) than QTH units, also LED (Blue Phase C5, UltraLume 5) generates obvious heat emission and temperature rises than QTH units (at 20 s) except for those which have lower power density of LED curing units (first generation). Thus, the null hypothesis was rejected. Keywords: Heat Emission of Light Curing Units